Proceedings of the 31st ACM International Conference on Design of Communication 2013
DOI: 10.1145/2507065.2507081
|View full text |Cite
|
Sign up to set email alerts
|

A customized mobile application for a cerebral palsy user

Abstract: Mobile web has created several opportunities for the development of assistive technologies that can support disabled people in the performance of daily life activities. Mobile applications can be developed using participatory design methods which result in customized assistive solutions. In this paper, we describe the development of a mobile application to support M, a man with cerebral palsy in his communication and professional activities, highlighting the use of a participatory design method. We discuss the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Besides, the literature review presenting herein other researches involving people with disabilities in the design process, which guided the development of PD4CAT, can be found in our papers presented in [1][2][3]13].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides, the literature review presenting herein other researches involving people with disabilities in the design process, which guided the development of PD4CAT, can be found in our papers presented in [1][2][3]13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Each phase of PD4CAT presents specific requirements that lead to the method's main goal. Those phases were proposed after a preliminary ethnographic study [3], where our team of computing science researchers observed the context of a rehabilitation institution for 6 months. We observed many therapeutic sessions involving therapists, patients, and caregivers.…”
Section: Pd4catmentioning
confidence: 99%
See 3 more Smart Citations